(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2012)
The present study was designed to investigate the impact of modernization on values of undergraduate students. The data were collected from 1000 undergraduate students with age from 17-22 years (500 Males and 500 Females) from rural, urban, and private and goverment degree colleges (affiliated to Guru Nanak Dev University, Amritsar), of Amritsar district. Proportionate Random sampling technique was used for the collection of data. The tools used were: A Battery of Modernization Scale by Kumari Radha Pandey(1984),Revised and modified Hindi adaptation of values by S.P. Kulshreshthta (1970).In order to study the impact of modernization on values of undergraduate students, one way ANOVA was computed along with Pearsons product moment correlation. The study revealed that there is significant positive correlation between modernization and Values and also there is significant impact of modernization on values of undergraduate students